Composite oxide catalyst and its preparation method and application

By using a composite oxide catalyst prepared in combination with the MoAl composite oxide with an ordered mesoporous structure and the oxides of V and Nb, the problem of insufficient low-temperature activity and selectivity in the ethane selection oxidation reaction is solved, efficient ethane conversion and the generation of high-value-added products are achieved, and the risks of COx generation and equipment corrosion are reduced.

CN116328755BActive Publication Date: 2025-02-28PETROCHINA CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202111582398.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-22
Publication Date
2025-02-28
Estimated Expiration
2041-12-22

AI Technical Summary

Technical Problem

In the prior art, it is difficult to obtain high conversion and high selectivity under low temperature conditions in the ethane selective oxidation reaction, and the catalyst activity is easy to decrease. Excessive deep oxidation reaction leads to an increase in COx generation and serious equipment corrosion.

Method used

MoAl composite oxide with an ordered mesoporous structure is used as the main active component to prepare a composite oxide catalyst. By combining it with the oxides of V and Nb, a catalyst of xMoaVbNbcOy is formed, and the activity and stability of the catalyst are improved through specific preparation methods and reaction conditions.

Benefits of technology

At lower reaction temperature, the conversion rate of ethane and the yield of acetic acid and ethylene are significantly improved, adapting to a larger system pressure range and higher spacespeed, reducing the generation of COx, reducing the risk of equipment corrosion, and realizing the integration of reaction separation, which significantly reduces the separation cost of industrial raw material gas.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003427434280000091
    Figure BDA0003427434280000091
  • Figure BDA0003427434280000101
    Figure BDA0003427434280000101
  • Figure HDA0003427434290000011
    Figure HDA0003427434290000011
Patent Text Reader

Abstract

The present invention discloses a composite oxide catalyst, a preparation method and an application thereof. The composite oxide catalyst uses oxides of metals Mo, V and Nb as main active components. The composite oxide catalyst is represented by: xMo a V b Nb c O y ; wherein the molar ratio of the metals Mo, V and Nb is a:b:c, a=1-5, b=1, c=0.1-1, y is the number of oxygens that satisfy the valence of each element in the composite oxide catalyst; the oxide of Mo is a MoAl composite oxide with an ordered mesoporous structure; x=1-10, x is represented by the molar percentage of the elements Mo:Al in the MoAl composite oxide. The composite oxide catalyst of the present invention can obtain a higher C2H6 conversion rate and acetic acid and ethylene yields at a lower reaction temperature, can be used for the direct selective oxidation reaction of ethane, and can obtain a better reaction result at a lower temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of multiphase catalyst preparation technology and catalytic reaction, and in particular to an ordered mesoporous molybdenum trioxide-doped composite oxide catalyst, a preparation method thereof, and application thereof in the direct oxidation of ethane to produce acetic acid and ethylene. Background Art

[0002] At present, most chemical raw materials come from petroleum resources. With the depletion of petroleum resources, the development of the petrochemical industry will face huge challenges. In recent years, the proven reserves of natural gas have continued to increase. According to relevant research data, by around 2010-2020, the reserves of natural gas will account for as much as 60% of the world's energy structure, which may replace the main position of oil in the world's energy structure. Ethane is the second component of natural gas. If ethane is catalytically converted into chemical raw materials such as olefins and oxygen-containing compounds, it can greatly alleviate the crisis of shortage of chemical raw materials. In 1978, E.M. Thorsteinson first proposed the use of MoVO x The catalyst system catalyzes the oxidative dehydrogenation of ethane to produce ethylene (Thorsteinson, TP Wilson, FG Young, PH Kasai, The oxidative dehydrogenation of ethane overcatalysts containing mixed oxides of molybdenum and vanadium, J. Catal. 1978, 52, 116-132.), and at a relatively low reaction temperature, ethylene and acetic acid can be obtained as a byproduct. MoVNbPO prepared by Saudi Basic Industries Corporation x The catalyst (US6013597A) exhibits excellent ethane selective oxidation performance at a reaction temperature of 260° C. Therefore, the Mo-V system catalyst is considered to be one of the best catalysts for ethane selective oxidation.

[0003] In the selective oxidation of ethane, it is necessary to improve the activity of the catalyst so that it can activate the CH bonds in low-carbon alkanes under relatively harsh reaction conditions, while also avoiding deep oxidation of the reactants to CO. x , thereby increasing the yield of the target product. Therefore, improving the ethane conversion rate while obtaining higher product selectivity is the key and difficulty for a successful reaction.

[0004] Mesoporous materials are a type of porous materials with the advantages of low density, high porosity, obvious surface effect, large specific surface area, good gas permeability and selective permeability, etc., and have broad application prospects in separation and purification, catalytic chemistry, biomaterials, assembly materials, etc. With the continuous and in-depth research on ordered mesoporous metal oxides, they have shown more advantages, such as variability of components and valence states, high specific surface area and through-hole network, regular and orderly pore structure and adjustable pore size, etc., showing great application potential in the field of catalysis. Porous transition metal oxides have unique physical and chemical properties, such as different valence electron layer configurations and valence states, more active sites brought by high specific surface area, and pore network structure that can promote the adsorption of reactant molecules and rapid diffusion of products. Therefore, the multi-component composite oxide catalyst prepared with mesoporous molybdenum oxide can effectively improve the catalytic activity of the catalyst for ethane selective oxidation and greatly improve its low-temperature catalytic performance.

[0005] Selective Oxidation of Ethane Over Mo-V-Al-O Oxide Catalysts: Insight to the Factors Affecting the Selectivity of Ethylene and Acetic Acid and Structure-activity Correlation Studies, (Catal. Lett., 2008, 121, 39-51.) The catalysts were characterized by XRD, SEM, Raman, UV-Vis and EPR techniques, and the MoVAlO x Chemical elements for the preparation of composite oxide catalysts. It was found that composite oxide catalysts with the general formula MoVAlO prepared with the same initial element composition x The final elemental composition of the catalysts was highly dependent on pH. The catalyst prepared at pH = 2 showed excellent activity for the selective oxidation of ethane, with an ethane conversion of 23% and a combined selectivity of 80.6% for ethylene and acetic acid, while the catalyst prepared at pH = 4 had the lowest activity. The higher activity of the catalysts was attributed to the MoV 2 O 8 and other reducing species (such as MoO 3 Phase transformation of Mo 4 O 11 The presence of partially reduced V and Mo ions in the presence of the phase) seems to play a crucial role in the selective oxidation of ethane. Although the excess steam co-feed improves the selectivity of acetic acid, it also reduces the conversion of ethane. The shortcomings of this technology or the shortcomings of the present invention are as follows: ① This technology systematically studies the MoVAlO xThe preparation chemical elements of composite oxide catalysts, but the influence of the relative proportion of active components on the performance of catalyst ethane oxidation reaction is lacking; ② In the research part of the reaction process of ethane oxidation to acetic acid, water vapor is used as diluent gas, and the proportion of water added to the raw gas is relatively high. The product acetic acid is easily soluble in water, and the generated dilute acetic acid solution will cause serious corrosion to the equipment. In addition, the use of air as an oxidant limits the proportion adjustment of each component in the raw gas; ③ This technology does not involve the research on the oxidation reaction of lower concentration ethane (such as natural gas, oil field associated gas, etc.).

[0006] Oxidation of ethane to ethylene and acetic acid by MoVNbO catalysts (Catal. Today, 2005, 99, 77–87.) The effects of niobium on the physical and chemical properties of the Mo-VO system and its catalytic properties in the oxidation of ethane to ethylene and acetic acid were studied in depth. Using in-situ XRD, XPS, Raman and LRS and other characterization methods, the influence mechanism of the preparation of catalyst precursors and the heat treatment process on the active phase of the catalyst for ethane oxidation was studied in detail, and it is believed that the synergistic effect between these structurally related oxides is the reason for the high selectivity. ; The defects of this technology or the shortcomings of the present invention are as follows: ① The focus is on the study of the material phase structure, and the research on the relationship between active species and the catalytic process of ethane oxidation reaction is less close; ② There is a lack of relevant research on the changes of active species on the catalyst surface and the process of adsorption and activation of raw materials; ③ There are too few data on the investigation of the process conditions of ethane selective oxidation reaction, and the reaction results are low, especially the ethane conversion rate.

[0007] In US Pat. No. 6,013,597, Catalysts for the oxidation of ethane to acetic acid processes of making same and processes of using same, an oxide catalyst containing the elements Mo, V and Nb and a small amount of phosphorus, boron, hafnium, Te and / or As is provided. The modified catalyst can obtain a higher selectivity and acetic acid yield in the low-temperature oxidation of ethane with a molecular oxygen-containing gas. In the presence of the improved catalyst, a method for producing acetic acid with higher selectivity by catalytic oxidation of ethane with oxygen is provided. ; The defects of this technology or the shortcomings of the present invention are as follows: ① This invention uses molybdenum, vanadium and niobium as the main active components, and adds P, B, Te, etc. to modify the catalyst. Among them, the MoVNbP series catalysts show good catalytic performance. However, many studies on the selective oxidation reaction of low-carbon alkanes have shown that P species are easily lost in long-term high-temperature reactions, resulting in reduced catalyst activity; ② MoVNbP catalysts can obtain a higher ethane conversion rate (up to 65%), but the oxygen content in the reaction raw materials is too high (17%, ethane is 15%), resulting in low selectivity for acetic acid and ethylene. And with air as the oxidant, the ratio of the reaction raw gas cannot be flexibly adjusted; ③ This technology uses N in the air as the oxidant. 2 It is a diluent gas, and the research on the selective oxidation reaction of ethane in other diluent gases (such as methane) is not involved. Summary of the invention

[0008] The object of the present invention is to provide a composite oxide catalyst and a preparation method and application thereof. The composite oxide catalyst is a multi-component metal oxide containing molybdenum trioxide with a mesoporous structure. The catalyst is used for the selective oxidation of ethane to produce acetic acid and ethylene, and a high C 2 H 6 The conversion rate and acetic acid and ethylene yields can adapt to a larger system pressure range and a higher space velocity. At the same time, due to the low reaction temperature, the deep oxidation reaction can be inhibited, effectively reducing CO x In addition, for a small amount of light hydrocarbons (ethane, propane, butane, etc.) in natural gas, the catalyst of the present invention is used for selective oxidation reaction, which can reduce impurities in raw gas while obtaining high value-added products, achieve the effect of reaction and separation integration, and significantly reduce the separation cost of industrial raw gas; the composite oxide catalyst can be used for direct selective oxidation of ethane, and can obtain better reaction results at a lower temperature.

[0009] In order to achieve the above object, the present invention provides a composite oxide catalyst, wherein the composite oxide catalyst has oxides of metals Mo, V, and Nb as main active components, and the composite oxide catalyst is represented by:

[0010] x a V b Nb c O y (Ι)

[0011] The molar ratio of the metals Mo, V and Nb is a:b:c, where a=1-5, b=1, c=0.1-1, and y is the number of oxygens satisfying the valence of each element in the composite oxide catalyst; the oxide of Mo is a MoAl composite oxide having an ordered mesoporous structure; and x=1-10, where x is expressed as the molar percentage of the elements Mo:Al in the MoAl composite oxide.

[0012] In the above composite oxide catalyst, in formula (I), a=1-5, b=1, c=0.1-1, wherein y is the number of oxygens satisfying the valence of each element in the composite oxide catalyst.

[0013] In the above composite oxide catalyst, preferably, the mesoporous structure of the MoAl composite oxide with an ordered mesoporous structure is regular and orderly; the average pore size of the mesopores of the MoAl composite oxide with an ordered mesoporous structure is preferably 7-30 nm.

[0014] In the above composite oxide catalyst, the average pore volume of the mesopores of the MoAl composite oxide having an ordered mesoporous structure is preferably 0.4-0.5 cm 3 ·g -1 The specific surface area of ​​the MoAl composite oxide having an ordered mesoporous structure is preferably 100-200m 2 ·g -1 .

[0015] The present invention also provides a method for preparing a composite oxide catalyst, the preparation method comprising the following steps:

[0016] The MoAl composite oxide with an ordered mesoporous structure is fully mixed with a solution containing V and Nb, and the solvent is slowly evaporated to obtain a dry solid; the dry solid is heat-treated in an air atmosphere to obtain a composite oxide catalyst.

[0017] In a preferred embodiment, the preparation method of the composite oxide catalyst specifically comprises the following steps:

[0018] (1) Preparation of MoAl composite oxide with ordered mesoporous structure: The calculated amount of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer was weighed and dissolved in an appropriate amount of anhydrous ethanol. Under vigorous stirring, the calculated amount of 67% HNO 3, m mol aluminum isopropoxide, and n mol ammonium molybdate are successively added to the above solution (wherein n / m=x / 100), the above mixture is stirred and transferred to a culture dish, and placed in a forced air drying oven for volatilization self-assembly process to obtain a light yellow dry gel, and then the dry gel is placed in a muffle furnace and raised to 600-800° C. at 1° C. / min, and calcined for 4-8 hours to obtain MoAl composite oxide powder A with an ordered mesoporous structure;

[0019] (2) Preparation of a solution containing V and Nb: a calculated amount of ammonium metavanadate is dissolved in an appropriate amount of deionized water to obtain an ammonium metavanadate suspension; a calculated amount of oxalic acid is slowly added to the aqueous solution of ammonium metavanadate under stirring at 80-100° C.; stirring is continued until the solution becomes an orange-yellow suspension B; a calculated amount of niobium oxalate is dissolved in an appropriate amount of deionized water; stirring is continued at 50-80° C. to obtain a white emulsion; the niobium oxalate emulsion is slowly added dropwise to the suspension B under stirring to obtain a yellow-green suspension; a calculated amount of oxalic acid is slowly added to the yellow-green suspension under stirring; the yellow-green suspension becomes a dark blue solution C;

[0020] (3) Preparation of composite oxide catalyst: Powder A is uniformly dispersed in an appropriate amount of deionized water to obtain dispersion A, solution C is added dropwise to dispersion A under stirring, the solvent is completely evaporated under stirring, dried, and calcined to obtain a composite oxide catalyst.

[0021] Further preferably, in step (1), the polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer is Pluronic P123, (EO) 20 (PO) 70 (EO) 20 .

[0022] Further preferably, in step (1), the stirring temperature is room temperature and the stirring time is 4-8 hours.

[0023] More preferably, in step (1), the volatilization temperature is 60-90° C., and the volatilization time is 24-48 hours.

[0024] Further preferably, in step (1), the calcination temperature is 600-800° C., the calcination time is 4-8 hours, and the calcination heating rate is 1-5° C. / min.

[0025] Further preferably, in step (3), the evaporation temperature of the solvent is 80-120°C.

[0026] Further preferably, in step (3), the drying temperature is 80-120° C., and the drying time is 12-24 h.

[0027] Further preferably, in step (3), the calcination temperature is 300-500° C., and the calcination time is 2-8 h.

[0028] The present invention further provides an application of a composite oxide catalyst in the selective oxidation of ethane to produce acetic acid and ethylene, the application comprising: using the composite oxide to catalyze the selective oxidation reaction of ethane in a mixed gas to achieve direct production of acetic acid and ethylene from ethane.

[0029] In the above application, preferably, the reaction conditions are: carried out at a pressure of 0.8-1.5 MPa, nitrogen and / or methane as diluent, reaction temperature of 220-260°C, gas space velocity of 300-1800 mL·g -1 ·h -1 , the gas space velocity is the total space velocity of ethane, oxygen and nitrogen, and the volume ratio of ethane to oxygen is 1-4.

[0030] Compared with the prior art, the composite oxide catalyst provided by the present invention has the following substantial advantages and characteristics:

[0031] 1. The catalyst provided by the present invention is doped with MoAl oxide having a mesoporous structure. The ordered mesoporous structure can make the active components of the catalyst more evenly distributed, increase the surface active sites, and improve the reaction efficiency.

[0032] 2. The catalyst provided by the present invention doped with mesoporous molybdenum trioxide oxide significantly improves the low-temperature catalytic activity and achieves a higher C 2 H 6 Conversion rate and CH 3 COOH and C 2 H 4 Selectivity, reducing CO x The reaction process can be effectively controlled, which has an important impact on improving the process of ethane selective oxidation to acetic acid and ethylene, and is more conducive to its industrial application.

[0033] 3. The catalyst provided by the present invention is prepared by a precipitation method. According to actual needs, the catalyst component ratio can be fine-tuned, the reaction parameters can be optimized, etc., to improve the adaptability of the catalyst to the reaction raw gas and flexibly control the distribution of the reaction products.

[0034] 4. The method for selective oxidation of ethane to produce acetic acid and ethylene provided by the present invention can be used in the reaction process of selective oxidation of a small amount of light hydrocarbons to produce olefins and oxygen-containing compounds in an atmosphere of nitrogen, methane, etc. Innovatively develop an integrated reaction and separation technology for light hydrocarbons such as oilfield natural gas and refinery gas, which reduces the separation energy consumption of low-carbon hydrocarbons while producing high-value-added chemicals.

[0035] The present invention has the following beneficial effects:

[0036] (1) The composite oxide catalyst provided by the present invention is a multi-component metal oxide catalyst prepared by using MoAl composite oxide with an ordered mesoporous structure as the main active component. The pore confinement effect of the ordered mesopores enables the catalyst to show excellent reaction performance in the selective oxidation of ethane to acetic acid and ethylene. The ordered mesoporous structure can also make the distribution of the active components of the catalyst more uniform, increase the surface active sites, and improve the reaction efficiency;

[0037] (2) The composite oxide catalyst provided by the present invention is used for the selective oxidation of ethane to produce acetic acid and ethylene, which significantly improves the low-temperature catalytic activity and can obtain a higher C at a lower reaction temperature. 2 H 6 The conversion rate and acetic acid and ethylene yields can adapt to a larger system pressure range and a higher space velocity. At the same time, due to the low reaction temperature, the deep oxidation reaction can be inhibited, effectively reducing CO x The generation of

[0038] (3) For a small amount of light hydrocarbons (ethane, propane, butane, etc.) in natural gas, the catalyst described in the present invention is used for selective oxidation reaction, which can reduce impurities in the raw gas while obtaining high value-added products, achieve the effect of integrated reaction and separation, and significantly reduce the separation cost of industrial raw gas. BRIEF DESCRIPTION OF THE DRAWINGS

[0039] Figure 1 This is a TEM image of the 5MoAl composite oxide in Example 1.

[0040] Figure 2 The multi-metal oxide 10Mo in Example 2 2.5 V 1 Nb 0.37 O y TEM images of the catalyst. DETAILED DESCRIPTION

[0041] The following is a detailed description of the embodiments of the present invention: This embodiment is implemented on the premise of the technical solution of the present invention, and a detailed implementation method and process are given, but the protection scope of the present invention is not limited to the following embodiments. The experimental methods in the following embodiments without specifying specific conditions are usually carried out under conventional conditions.

[0042] Example 1

[0043] This embodiment provides a composite oxide catalyst A1, wherein the catalyst is prepared by the following method:

[0044] Step 1: Weigh 42.0 g of P123 and dissolve it in 600 mL of anhydrous ethanol. Add 50 mL of 67% HNO 3 , 81.7 g of C9 H 21 AlO 3 , 3.5 g of (NH 4 ) 6 Mo 7 O 24 ·4H 2 O was slowly added to the above solution, and the above mixture was stirred for 6 hours at room temperature, then transferred to a petri dish, and placed in a forced air drying oven at 60°C for 48 hours for volatilization self-assembly process to obtain a light yellow dry gel. Then, the dry gel was placed in a muffle furnace and heated to 600°C at 1°C / min, and calcined for 6 hours to obtain mesoporous 5MoAl oxide powder.

[0045] Step 2: 1.17 g of NH 4 VO 3 Dissolve in 15 mL of deionized water to obtain a suspension of ammonium metavanadate. Slowly add 0.25 g of H 2 C 2 O 4 ·2H 2 O, continue stirring the solution to turn into an orange-yellow suspension; add 2.7 g of C 10 H 5 NbO 20 ·xH 2 O was dissolved in 10 mL of deionized water and stirred at 60 °C to obtain a white emulsion. The niobium oxalate emulsion was slowly added dropwise to the orange-yellow suspension and stirred to obtain a yellow-green suspension. Under stirring, 2.87 g of H 2 C 2 O 4 ·2H 2 O, the yellow-green suspension turned into a dark blue solution.

[0046] Step 3: Evenly disperse the 5MoAl powder obtained in step 1 into 50 mL of deionized water, slowly drop the dark blue solution obtained in step 2 into the dispersion under stirring, completely evaporate the solvent under stirring at 90°C, dry at 120°C for 24 hours, and then calcine at 400°C for 4 hours to obtain 5MoAl. 2 V 1 Nb 0.5 O y catalyst.

[0047] The mesoporous 5MoAl oxide powder obtained in step 1 was tested. 2 The adsorption-desorption test results show that the average pore diameter is 9.5 nm and the average pore volume is 0.47 cm 3 ·g -1 , with a specific surface area of ​​179.8m 2 ·g -1 .

[0048] Example 2

[0049] This embodiment provides a composite oxide catalyst A2, wherein the catalyst is prepared by the following method:

[0050] Step 1: Weigh 55.0 g of P123 and dissolve it in 800 mL of anhydrous ethanol. Add 64 mL of 67% HNO 3 , 102.1 g of C 9 H 21 AlO 3 , 8.82 g of (NH 4 ) 6 Mo 7 O 24 ·4H 2 O was slowly added to the above solution, and the above mixture was stirred at room temperature for 8 hours, then transferred to a petri dish, placed in a forced air drying oven at 65°C for 36 hours for volatilization self-assembly process, and a light yellow dry gel was obtained. Then, the dry gel was placed in a muffle furnace and heated to 700°C at 1°C / min, and calcined for 5 hours to obtain mesoporous 10MoAl oxide powder.

[0051] Step 2: 2.34 g of NH 4 VO 3 Dissolve in 25 mL of deionized water to obtain a suspension of ammonium metavanadate. Slowly add 0.5 g of H 2 C 2 O 4 ·2H 2 O, continue stirring the solution to turn into an orange-yellow suspension; add 4.0 g of C 10 H 5 NbO 20 ·xH 2 O was dissolved in 20 mL of deionized water and stirred at 65 °C to obtain a white emulsion. The niobium oxalate emulsion was slowly added dropwise to the orange-yellow suspension and stirred to obtain a yellow-green suspension. Under stirring, 5.8 g of H 2 C 2 O 4 ·2H 2 O, the yellow-green suspension turned into a dark blue solution.

[0052] Step 3: Evenly disperse the 10MoAl powder obtained in step 1 into 65mL of deionized water, slowly drop the dark blue solution obtained in step 2 into the dispersion under stirring, completely evaporate the solvent under stirring at 95°C, dry at 110°C for 24h, and then calcine at 350°C for 5h to obtain 10MoAl 2.5 V 1 Nb0.37 O y catalyst.

[0053] The mesoporous 10MoAl oxide powder obtained in step 1 was tested. 2 The adsorption-desorption test results show that the average pore size is 30.0 nm and the average pore volume is 0.40 cm 3 ·g -1 , with a specific surface area of ​​112.4m 2 ·g -1 .

[0054] Comparative Example 1

[0055] This comparative example provides a composite oxide catalyst B. To compare the effect of mesoporous molybdenum trioxide doping on the catalyst performance, ammonium molybdate was used to replace 10MoAl in Example 2 to prepare a catalyst with the same composition. The catalyst was prepared by the following method:

[0056] Step 1: 17.1 g of NH 4 VO 3 Dissolve in 200 mL of deionized water to obtain a suspension of ammonium metavanadate. Slowly add 3.75 g H 2 C 2 O 4 ·2H 2 O, continue stirring the solution to turn into an orange-yellow suspension; add 29.1 g of C 10 H 5 NbO 20 ·xH 2 O was dissolved in 150 mL of deionized water and stirred at 60 °C to obtain a white emulsion.

[0057] Step 2: slowly drop the niobium oxalate emulsion in step 1 into the suspension of ammonium metavanadate and continue stirring to obtain a yellow-green suspension. While stirring, slowly add 45 g of H 2 C 2 O 4 ·2H 2 O, the yellow-green suspension turned into a dark blue solution.

[0058] Step 3: 64.8 g of (NH 4 ) 6 Mo 7 O 24 ·4H 2 O was dissolved in 75 mL of deionized water and stirred at 60 °C to obtain a colorless solution.

[0059] Step 4: slowly drop the colorless ammonium molybdate solution synthesized in step 3 into the dark blue solution synthesized in step 2 to generate a precipitate, completely evaporate the solvent at 90°C, dry at 110°C for 24h, and then calcine at 400°C for 2h to obtain a multi-metal oxide Mo 2.5 V 1 Nb 0.37 O y catalyst.

[0060] Example 3

[0061] The catalysts obtained in Examples 1-2 and Comparative Example 1 are used in the direct production of acetic acid and ethylene from ethane, and the reaction process comprises the following steps:

[0062] The catalyst A1 provided in Example 1, the catalyst A2 provided in Example 2 and the catalyst B provided in Comparative Example 1 were used in a pressurized stainless steel fixed bed reactor to catalyze the selective oxidation of ethane to produce acetic acid and ethylene. The reaction was carried out at a system pressure of 1.2 MPa, nitrogen was used as a diluent, the reaction temperature was 225-255°C, and the total gas space velocity of the feed gas was 600 h -1 , the volume ratio of ethane to oxygen is 2. The inner diameter of the reaction tube is 8 mm.

[0063] The reaction products were analyzed online by gas chromatography and by FID (flame ionization detector). 2 H 4 , CH 3 COOH, O analyzed by TCD (thermal conductivity detector) 2 、N 2 , C 2 H 6 , C 2 H 4 ,CO,CO 2 The correction factor area normalization method was used to calculate C 2 H 6 Conversion rate and CH 3 COOH and C 2 H 4 The selectivity, etc., the performance evaluation results are shown in Table 1 below.

[0064] Table 1

[0065]

[0066]

[0067] From the results in Table 1, it can be seen that the composite oxide catalyst of the present invention uses the MoAl composite oxide with an ordered mesoporous structure, which improves the C 2 H6 Conversion rate and yield of acetic acid and ethylene.

Claims

1. Use of a composite oxide catalyst in the selective oxidation of ethane to produce acetic acid and ethylene, characterized in that: The composite oxide catalyst has oxides of metals Mo, V and Nb as main active components, and the composite oxide catalyst is represented by: xMo a V b Nb c O y (I) The molar ratio of the metals Mo, V and Nb is a:b:c, where a=1-5, b=1, c=0.1-1, and y is the number of oxygens that satisfy the valence of each element in the composite oxide catalyst; the oxide of Mo is a MoAl composite oxide having an ordered mesoporous structure; x=1-10, where x is the molar percentage of the elements Mo:Al in the MoAl composite oxide; The preparation method of the MoAl composite oxide having an ordered mesoporous structure comprises the following steps: Weigh a calculated amount of polyethylene oxide-polypropylene oxide-polyethylene oxide triblock copolymer, dissolve it in an appropriate amount of anhydrous ethanol, add a calculated amount of HNO3, m mol of aluminum isopropoxide, and n mol of ammonium molybdate to the solution in succession under vigorous stirring, wherein n / m=x / 100, stir the above mixture and transfer it to a culture dish, place it in a forced air drying oven for volatilization self-assembly process, and obtain a light yellow dry gel, then, calcine the dry gel in a muffle furnace, and obtain a MoAl composite oxide powder with an ordered mesoporous structure; The mesoporous structure of the MoAl composite oxide with an ordered mesoporous structure is regular and orderly; the average pore size of the mesopores of the MoAl composite oxide with an ordered mesoporous structure is 7-30 nm; The average pore volume of the mesopores of the MoAl composite oxide having an ordered mesoporous structure is 0.4-0.5 cm 3 ·g -1 The specific surface area of ​​the MoAl composite oxide having an ordered mesoporous structure is 100-200m 2 ·g -1 ; The preparation method of the composite oxide catalyst comprises the following steps: The MoAl composite oxide with an ordered mesoporous structure is fully mixed with a solution containing V and Nb, and the solvent is slowly evaporated to obtain a dry solid; the dry solid is heat-treated in an air atmosphere to obtain a composite oxide catalyst.

2. The use according to claim 1, characterized in that: The preparation method of the composite oxide catalyst specifically comprises the following steps: (1) Preparation of a solution containing V and Nb: a calculated amount of ammonium metavanadate is dissolved in an appropriate amount of deionized water to obtain an ammonium metavanadate suspension; a calculated amount of oxalic acid is slowly added to the aqueous solution of ammonium metavanadate under stirring at 80-100° C.; stirring is continued until the solution becomes an orange-yellow suspension B; a calculated amount of niobium oxalate is dissolved in an appropriate amount of deionized water; stirring is continued at 50-80° C. to obtain a white emulsion; the niobium oxalate emulsion is slowly added dropwise to the suspension B under stirring to obtain a yellow-green suspension; a calculated amount of oxalic acid is slowly added to the yellow-green suspension under stirring, and the yellow-green suspension becomes a dark blue solution C; (2) Preparation of composite oxide catalyst: MoAl composite oxide powder with an ordered mesoporous structure is uniformly dispersed in an appropriate amount of deionized water to obtain dispersion A, solution C is added dropwise to dispersion A under stirring conditions, the solvent is completely evaporated under stirring, dried, and calcined to obtain a composite oxide catalyst.

3. The use according to claim 1, characterized in that: In the preparation method of the MoAl composite oxide with an ordered mesoporous structure, the stirring temperature during the process of transferring the above mixture to a culture dish after stirring is room temperature, and the stirring time is 4-8 hours; the volatilization temperature is 60-90°C, and the volatilization time is 24-48 hours; the calcination temperature is 600-800°C, the calcination time is 4-8 hours, and the calcination heating rate is 1-5°C / min.

4. The use according to claim 1, characterized in that: In the preparation method of the MoAl composite oxide with an ordered mesoporous structure, the calcination process is: increasing the temperature to 600-800° C. at 1° C. / min and calcining for 4-8 hours.

5. The use according to claim 2, characterized in that: In step (2), the evaporation temperature of the solvent is 80-120°C; the drying temperature is 80-120°C, and the drying time is 12-24h; the roasting temperature is 300-500°C, and the roasting time is 2-8h.

6. The use according to claim 1, characterized in that: The composite oxide catalyst catalyzes the selective oxidation reaction of ethane in the mixed gas to realize the direct production of acetic acid and ethylene from ethane; the reaction conditions are: carried out at a pressure of 0.8-1.5 MPa, nitrogen and / or methane as diluent gas, a reaction temperature of 220-260°C, and a gas space velocity of 300-1800 mL·g -1 ·h -1 , the gas space velocity is the total space velocity of ethane, oxygen and nitrogen, and the volume ratio of ethane to oxygen is 1-4.

Citation Information

Patent Citations

  • Catalysts for the oxidation of ethane to acetic acid processes of making same and, processes of using same

    US6013597A